The distribution of 14C and 39Ar in the Weddell Sea - Schlosser, P.; Kromer, B.; Weppernig, R.; Loosli, H.H.; Bayer, R.; Bonani, G.; Suter, M. (Journal of Geophysical Research, 1994)
Carbon 14 and 39Ar data from the Weddell Sea are presented and discussed. Values of Δ 14C and 39Ar are low in the winter mixed layer (Δ 14C ≈ −90 to −125‰; 39Ar ≈ 85 % modern). These low values are consistent with the surface layer dynamics which is dominated by entrainment of relatively old water of circumpolar origin and reduced gas exchange during sea ice cover. The Δ 14C and 39Ar values of the deep and bottom waters range from −160 to −150‰ and 38 to 57% modern, respectively. The Δ 14C values of Weddell Sea Bottom Water (WSBW) found in the central Weddell Sea along a 0° longitude section are only slightly higher than those of the overlying Weddell Sea Deep Water (WSDW) showing that the influence of bomb 14C on these waters is small. Part of the WSBW with higher Δ 14C values observed in the northwestern Weddell Sea seems to escape through the South Sandwich Trench, and part seems to mix from a boundary current into the central Weddell Sea. The observed 14C distribution is consistent with the hypothesis that Ice Shelf Water (ISW) is a source of WSBW. A simple conceptual model of the surface layer dynamics is used to estimate the prebomb Δ 14C values of Surface Water and Winter Water to be about −140 and −130‰, respectively. Using mixing ratios between WSDW and shelf water derived from temperature/salinity and 3He data, the prebomb Δ 14C values of WSBW are estimated to be −157‰ (potential temperature of WSBW: −0.7°C). The 39Ar concentration of WSBW with a potential temperature of −0.7°C is determined to be 57% modern. Bomb radiocarbon water column inventories are estimated and discussed.